A review on mechanisms of action of bioactive peptides against glucose intolerance and insulin resistance - Forough Jahandideh; Jianping Wu (Food Science and Human Wellness, 2022)
Insulin resistance leads to impaired glucose metabolism by disrupting both insulin secretion and sensitivity. Insulin resistance plays a key role in the pathophysiology of type 2 diabetes and metabolic syndrome. Reviews on the mechanisms of action of bioactive peptides on glucose homeostasis and insulin resistance are scarce. The recent discoveries of pathways and target cells in the management of glucose and energy metabolism have opened up new opportunities for identification of novel bioactive peptides on enhancing adipocyte differentiation and insulin signaling, glucose uptake, cholecystokinin receptor expression and activation, as well as insulin mimetics and incretin stimulants. Examples of food-derived bioactive peptides with glucoregulatory properties include Trp-Glu-Lys-Ala-Phe-Lys-Asp-Glu-Asp (WEKAFKDED), Gln-Ala-Met-Pro-Phe-Arg-Val-Thr-Glu-Gln-Glu (QAMPFRVTEQE), Glu-Arg-Tyr-Pro-Ile-Leu (ERKPIL), Val-Phe-Lys-Gly-Leu (VFKGL), Phe-Leu-Val (FLV), Val-Pro-Pro (VPP), Ile-Arg-Trp (IRW), Ala-Lys-Ser-Pro-Leu-Phe (AKSPLF), Ala-Thr-Gln-Pro-Leu-Phe (ATNPLF), Phe-Glu-Glu-Leu-Gln (FEELN), Leu-Ser-Val-Ser-Val-Leu (LSVSVL), Val-Arg-Ileu-Arg-Leu-Leu-Gln-Arg-Phe-Asn-Lys-Arg-Ser (VRIRLLQRFNKRS), and Ala-Gly-Phe-Ala-Gly-Asp-Asp-Ala-Pro-Arg (AGFAGDDAPR). However, as yet, clinical evidence on the efficacy of such bioactive peptides is rare but is inevitable to establish their applications against glucose intolerance and insulin resistance.